Seduction and conquest: A reading of Guamán Poma - Osorio, Alejandra (1990)
Virginity —and its loss— by Andean women constitutes one of the central themes of the Letter that Guamán Poma left for the King of Spain, Philip III, entitled New Chronicle and Good Government, for the year 1615. For Guamán Poma the virginity embodied in the acllacuna was synonymous with order and greatness, while the violation of this virginity is presented as the central paradigm of the social catastrophe —"the world turned upside down"— that the conquest brought to the Andean peoples.